PENGGUNAAN QAWA‘ID FIQHIYYAH DALAM PUTUSAN HAKIM DI PENGADILAN AGAMA MEDAN - Dedi Mahruzani Nur Lubis (TAQNIN: Jurnal Syariah dan Hukum, 2020)
This article discusses the extent of the use of Qawaid Fiqhiyyah in the Medan District Court Judgment. Qawaid Fiqhiyyah will look its function when someone or a mujtahid even a judge in court when facing problems of Islamic law. One of the official government agencies that always faces cases and problems of Islamic law is the Religious Court. The Religious Courts in resolving disputes under their jurisdiction desperately need the qawa>idh fiqhiyyah. The qawa>idh fiqhiyyah to be referred by a Judge of the Religious Courts in their decisions will assist them in resolving the cases at hand. In its legal considerations, the judge will normatively mention the qawa>idh fiqhiyyah as a reference in deciding a case. There are three decisions that are examined in this article about the extent of the use of fiqh rules in a Judge's decision in the Medan Religious Court.